Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Investigation regarding the correlation of the relative influences during the extrusion process of cast films on the residual melt quality - Schöppner, Volker; Trienens, Dorte

Material-Preserving Extrusion of Polyamide on a Twin-Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Schall, Christoph Wilhelm Theodor; Wanke, Sven; Kley, Marina (Polymers)

Modellierung der Feststoffförderung im Einzug von Nutbuchsenextrudern mit Hilfe von DEM-Simulationen - Brüning, Florian
Bei der Auslegung von Einschnecken-Plastifizierextrudern mit genutetem Einzug sind Simulationen ein gängiges Mittel, um zeit-, ressourcen- und kostenintensive experimentelle Untersuchungen einzusparen. Bestehende mathematisch-physi-kalische Berechnungsmodelle auf Basis analytischer Gleichungen weisen jedoch einige Annahmen und Vereinfachungen auf, die die Qualität der rechnerischen Vorhersage reduzieren können. Diese Arbeit liefert daher einen Beitrag, indem analytische Modelle zur Berechnung des Druck-Durchsatz-Verhaltens und der Antriebsleistung in genuteten Einzugszonen mithilfe von numerischen Simulatio-nen basierend auf der Diskrete-Elemente-Methode (DEM) überprüft werden. Es wird gezeigt, dass die Annahme eines gegendruckunabhängigen Durchsatzver-haltens sowie die Unterscheidung in form- und reibschlüssige Förderfälle ge-rechtfertigt ist. Die Annahme einer Blockströmung ist oft nicht gerechtfertigt, auch wenn dies nicht notwendigerweise zu Abweichungen in der Durchsatzberech-nung führt. Für die analytische Durchsatz- und Leistungsberechnung werden re-gressionsbasierte Korrekturfaktoren eingeführt, die die Vorhersagegenauigkeit steigern. Weiterführende Untersuchungen zeigen, unter welchen Bedingungen und mit welchen Maßnahmen sich der Durchsatz von genuteten Einzugszonen steigern lässt. Schließlich wird eine Methode zur Kalibrierung von DEM-Simula-tionen vorgestellt, mit welcher sich die Abbildungsgenauigkeit des tribologischen Verhaltens des Schüttguts erhöhen lässt.

Untersuchung der UVC-Bestrahlung als Oberflächenvorbehandlungsmethode von Polycarbonaten zur Erzeugung einer Verbundhaftung zu Flüssigsilikonkautschuken - Hartung, Michael

An approach for the numerical calculation of the non-isothermal pressure-throughput-characteristics of single screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of the influence of process and screw configurations on fiber length for recycled carbon fiber - Malatyali, Hatice; Schöppner, Volker; Hoemann, Theresa (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of shear rates in twin-screw extruder using CFD-simulation - Malatyali, Hatice; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Influence of fiber geometry and sizing on glass fiber breakage - Bürenhaus, Franziska Isabelle; Moritzer, Elmar (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Downwind and upwind approximations for mesh and model adaptivity of elasto‐plastic composites - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract The use of heterogeneous materials, such as composites with Prandtl‐Reuss‐type material laws, has increased in industrial praxis, making finite element modeling with homogenization techniques a well‐accepted tool. These methods are particularly advantageous to account for microstructural mechanisms which can be related to nonlinearities and time‐dependency due to elasto‐plasticity behavior. However, their advantages are diminished by increasing computational demand. The present contribution deals with the balance of accuracy and numerical efficiency of nonlinear homogenization associated with a framework of goal‐oriented adaptivity, which takes into account error accumulation over time. To this end, model adaptivity of homogenization methods is coupled to mesh adaptivity on the macro scale. Our new proposed adaptive procedure is driven by a goal‐oriented a posteriori error estimator based on duality techniques using downwind and upwind approximations. Due to nonlinearities and time‐dependency of the plasticity, the estimation of error transport and error generation is obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Finally, a numerical example illustrates the effectiveness of the proposed adaptive approach.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics